MON-516 Skeletal Fluorosis from Fluorocarbon Inhalation - Seagrove-Guffey, Maighan (J Endocr Soc, 2019)
Background: Skeletal fluorosis (SF) is endemic in many places, especially where well water is rich in fluoride (F) from volcanic rock. SF is rare in the US, where it has unusual causes. The impact of F on the skeleton is conditioned by calcium and vitamin D sufficiency. Clinical Case: A 51-year-old obese man with chronic opiate use was referred for secondary hyperparathyroidism detected after right femoral neck and left proximal femur fractures, and displaced humeral fracture which healed poorly with radial nerve entrapment. Oncologic evaluation was negative, including intraoperative bone biopsy. He reported longstanding diffuse musculoskeletal pain, drank 72 oz of cola daily, and consumed little dietary calcium. Physical exam showed Ht 1.7 m, BMI 46, no dental abnormalities, deformed right humerus, diminished right wrist dorsiflexion, and an antalgic gait. DXA BMD Z-score was +7.4 at the spine and +0.4 at the “1/3” radius. At femur fracture, corrected serum calcium was 7.8 mg/dL (8.5-10.1) and alkaline phosphatase (ALP) 1080 U/L (46-116). After 5 months of calcium and vitamin D supplementation, calcium was 9.4 mg/dL, ALP 539 U/L, phosphorus 3.7 mg/dL (2.3-4.7), 25(OH)D 20.6 ng/mL (30-100), PTH 327 pg/mL (8.7-77.1), and creatinine 0.62 mg/dL (0.72-1.25). Hepatitis C Ab and PSA were normal. Elevated serum C-telopeptide 2513 pg/mL (87-345) and osteocalcin greater than 300 ng/mL (9-38) indicated rapid bone turnover. Bone scan showed increased uptake at the left hip fracture site, 2 ribs, and periarticular areas. Radiographic skeletal survey revealed diffuse osteosclerosis. Mutation analysis for high turnover sclerotic skeletal disease was negative, including examination of OPG, exon 1 of RANK and a NSG high bone mass panel. Initially, F exposure history was negative, however serum and urine F levels were elevated at 118 mcmol/L (0-4) and 42.6 mg/L (0.3-3.2), respectively. His mother confided that he had “huffed” difluoroethane containing computer cleaner for 2 years several times daily to control pain. Subsequently, right femur fracture required intramedullary fixation, several weeks rehabilitation, and generous doses of calcium and vitamin D3. Routine nondecalcified histology showed reactive bone with reticulin and collagen fibrosis. 24-hour urine of 3.43 liters contained calcium less than 68.6 mg and F 91.6 mg (0.2-3.2 mg/L). Conclusion: Inhalant abuse of fluorocarbons is known. However, literature concerning the skeletal effects is scant. Our patient’s positive bone balance together with low calcium intake could explain his secondary hyperparathyroidism. High phosphorus in colas may also have decreased gastrointestinal calcium absorption. Deposition of fluorohydroxyapatite in the skeleton likely explained our patient’s skeletal fragility.